A importância do ranking do enem para a sociedade e as diferenças entre as redes de ensino - Bessa, Jonysin Tobias de Sousa (Universidade Federal Rural do Semi-Árido, 2017)
The school plays a very important role in society, from the transmission of basic knowledge of curricular subjects to the formation of being a citizen, extracting the best of the students, educating them and teaching them the scientific knowledge necessary to become autonomous and able to enter an academic life. But unfortunately, some schools in Brazil rely on outcomes, not focusing on the student’s formation as citizens. And since the Exame Nacional do Ensino Médio (ENEM) is the main gateway for young people into universities, each school has been concerned with preparing its students for this exam. In addition, each year, Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (INEP) publishes a ranking that presents the grades of students in their last year of high school, per teaching institution, which originated a huge dispute among schools for the best positions, to the point that many institutions create another CNPJ to mask the result obtained. The imposed competition and the need to achieve prominence among institutions have negatively affected not only educational institutions, but teachers, students and parents who are part of the school community. Therefore, this research precisely wants to evaluate the reality of the data presented by INEP, taking into consideration that many factors influence the outcome of an institution and show that not always the best placed school is necessarily a good school for our children. Another factor that will also be analyzed is the sad reality of the public schools according to this ranking, as well as the reasons that may cause the divergence in relation to their results compared to private schools
Keywords: ENEM; Ranking; Escolas; ENEM; Ranking; Schools; CIENCIAS EXATAS E DA TERRA::MATEMATICA